A decision support system for predicting settling velocity of spherical and non-spherical particles in Newtonian fluids. (4th July 2022) - Rushd, Sayeed; Rahman, Moklesur; Arifuzzaman, Mohammad; Aktaruzzaman, Md
Abstract: An artificial intelligence-based system was developed to efficiently predict settling velocity (SV) using a large dataset comprised of 2726 samples. The ranges of particle size and fluid viscosity were 0.212 − 98.59 mm and 0.02 − 92800 mPa.s, respectively. Properties of particle and fluid were fed to a model as the inputs to obtain SV as the output. Six machine learning algorithms were tested for the prediction. The random forest (RF) performed better than other algorithms with a coefficient of determination of 0.98 and a mean square error of 0.0027. A simple decision support system was developed using the RF model. The current study demonstrates the complete methodology of modeling SV with ML.